ANALISIS MINAT INVESTASI HIJAU PADA GENERASI MILENIAL DAN GENERASI Z DENGEN PENERAPAN KONSEP THEORY PLANNED OF BEHAVIOUR - Zulistiawati, Fauziah; Heryahya, Andang; Indriani (Universitas Airlangga, 2024)
The topic of eco-friendly products is a trending topic today, especially among Generation Z and millennials. One of them is about green investment. This investment is here to help answer the issue of our current environmental problems. With this green investment, it is hoped that it can support environmental sustainability and can support companies to be able to switch from environmentally friendly resources to environmentally friendly resources. The purpose of this study is to find out the factors that affect the interest in green investment among the Millennial Generation and Generation Z in Bogor. This research was analyzed using the Structural Equation Model (SEM) through SEMPLS 4.0.0 software. The results of the study show that attitudes towards green investment and behavioral control have a significant influence on green investment interest in Generation Z and millennials. Meanwhile, subjective norms do not have a significant effect on green investment intentions. It can be concluded that generation Z and millennials have a positive and good attitude and self-control towards green investment interest. However, the norms or habits in their environment cannot affect their interest in green investment